When Animosity Becomes Action: Understanding McDonald's Boycott in Indonesia - Louis Utama; Elviana (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study examines how consumer animosity influences boycott intention toward McDonald’s in Indonesia by testing cognitive judgment and affective evaluation as mediating variables and xenocentrism as a moderating variable. Design/methodology/approach – A quantitative explanatory and cross-sectional survey design was employed. Data were collected from 150 consumers in the Jabodetabek area who were aware of and participated in the McDonald’s boycott. Respondents were selected through purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 3.0 and a bootstrapping procedure involving 5,000 resamples. Findings/Results – The results show that consumer animosity significantly reduces cognitive judgment and affective evaluation, while strongly increasing boycott intention. Cognitive judgment negatively affects boycott intention and partially mediates the relationship between consumer animosity and boycott intention. In contrast, affective evaluation does not significantly influence boycott intention and does not function as a mediator. Xenocentrism does not moderate the relationship between consumer animosity and boycott intention, although it has a significant direct effect on boycott intention. The model explains 64.8% of the variance in boycott intention. Originality/Value –This study extends the consumer animosity literature by demonstrating that boycott intention in the Indonesian context is driven more by cognitive and ethical evaluation than by affective response alone. It also provides empirical evidence from an underrepresented Southeast Asian context and offers practical insight for multinational brands facing politically and morally charged consumer resistance.